(untitled) (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2015)
Today medical ontologies have an important role in medicine field to represent medical knowledge. They are much stronger than biomedical vocabularies. In diseases diagnosis process, each disease has number of symptoms associated with it. We can employ ontology in helping to diagnose diseases by building Diseases-Symptoms ontology, which relate diseases and symptoms. Such ontology would be very useful for medical expert systems to assist physicians in diagnosis diseases or as a training tool for medical students. In this paper, we propose a method that automatically extract medical knowledge from Web resources and build Diseases-Symptoms ontology. We use the linguistic pattern and statistical analysis techniques based on Bing search engine. We evaluated the proposed method for two diseases Hyperthyroidism and Eczema by two consultant physicians.